Characterization of neuromyelitis optica and neuromyelitis optica spectrum disorder patients with a late onset. (July 2014) - Collongues, N; Marignier, R; Jacob, A; Leite, MI; Siva, A; Paul, F; Zephir, H; Akman-Demir, G; Elsone, L; Jarius, S; Papeix, C; Mutch, K; et al.
Background: Few data are available for patients with a late onset (≥ 50 years) of neuromyelitis optica (LONMO) or neuromyelitis optica spectrum disease (LONMOSD), defined by an optic neuritis/longitudinally extensive transverse myelitis with aquaporin-4 antibodies (AQP4-Ab). Objective: To characterize LONMO and LONMOSD, and to analyze their predictive factors of disability and death. Methods: We identified 430 patients from four cohorts of NMO/NMOSD in France, Germany, Turkey and UK. We extracted the late onset patients and analyzed them for predictive factors of disability and death, using the Cox proportional model. Results: We followed up on 63 patients with LONMO and 45 with LONMOSD during a mean of 4.6 years. This LONMO/LONMOSD cohort was mainly of Caucasian origin (93%), women (80%), seropositive for AQP4-Ab (85%) and from 50 to 82.5 years of age at onset. No progressive course was noted. At last follow-up, the median Expanded Disability Status Scale (EDSS) scores were 5.5 and 6 in the LONMO and LONMOSD groups, respectively. Outcome was mainly characterized by motor disability and relatively good visual function. At last follow-up, 14 patients had died, including seven (50%) due to acute myelitis and six (43%) because of opportunistic infections. The EDSS 4 score was independently predicted by an older age at onset, as a continuous variable after 50 years of age. Death was predicted by two independent factors: an older age at onset and a high annualized relapse rate. Conclusion: LONMO/LONMOSD is particularly severe, with a high rate of motor impairment and death.